EFEKTIFITAS MENGAYUH SEPEDA UNTUK MENINGKATKAN KEMAMPUAN OTOT KAKI DALAM BERJALAN PADA ANAK TUNAGRAHITA SEDANG - Tiara Mardiah; Fatmawati Fatmawati; Ganda Sumekar (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by the problems that found a moderate mental retardation child's in preparation class X have problems in walking ability. This study uses the approach single research subject, ABA design and data analysis techniques using visual analysis chart. The results of this study concluded that riding a bike can improve the ability of the leg muscles in walking for a moderate mental retardation.